Reevaluation of Protein Intake for Preterm Infants - Kawai, Masahiko (American Journal of Perinatology, 2018)
Growth failure caused by undernutrition is considered one of the major causes for psychomotor delay in extremely preterm infants, and the concept for “aggressive nutritional approach” is widely accepted worldwide. Based on this, postnatal early catch-up growth due to sufficient supply of nutrients including sufficient amounts of amino acids is believed to be essential for a better outcome; however, there is no definitive evidence of aggressive nutrition on better outcomes in mortality, growth, and neurodevelopment. On the contrary, epidemiological evidence suggests that low birth weight and a rapid catch-up growth after birth are major risk factors for insulin resistance and diabetes in later life; higher protein intake during postnatal period relates to higher cardiovascular risk in later life. Considering these, optimal nutrition, especially protein administration, should be reevaluated. In this review, current opinions on the nutrition for the preterm infants are surveyed. In addition, I propose a new concept for optimized protein amount for the preterm infants based on the difference of amino acid metabolism between fetuses and preterm infants.
Keywords: nutrition; amino acid; preterm infants; fetus; urea cycle